Radioresistance, DNA Damage and DNA Repair in Cells With Moderate Overexpression of RPA1 - Velegzhaninov, Ilya O.; Belykh, Elena S.; Rasova, Elena E.; Pylina, Yana I.; Shadrin, Dmitry M.; Klokov, Dmitry Yu. (Frontiers in Genetics, 2020)
Molecular responses to genotoxic stress, such as ionizing radiation, are intricately complex and involve hundreds of genes. Whether targeted overexpression of an endogenous gene can enhance resistance to ionizing radiation remains to be explored. In the present study we take an advantage of the CRISPR/dCas9 technology to moderately overexpress the RPA1 gene that encodes a key functional subunit of the replication protein A (RPA). RPA is a highly conserved heterotrimeric single-stranded DNA-binding protein complex involved in DNA replication, recombination and repair. Dysfunction of RPA1 is detrimental for cells and organisms and can lead to diminished resistance to many stress factors. We demonstrate that HEK293T cells overexpressing RPA1 exhibit enhanced resistance to cell killing by gamma-radiation. Using the alkali comet assay, we show a remarkable acceleration of DNA breaks rejoining after gamma-irradiation in RPA1 overexpressing cells. However, the spontaneous rate of DNA damage was also higher in the presence of RPA1 overexpression, suggesting alterations in the processing of replication errors due to elevated activity of the RPA protein. Additionally, the analysis of the distributions of cells with different levels of DNA damage showed a link between the RPA1 overexpression and the kinetics of DNA repair within differentially damaged cell subpopulations. Our results provide knew knowledge on DNA damage stress responses and indicate that the concept of enhancing radioresistance by targeted alteration of the expression of a single gene is feasible, however undesired consequences should be considered and evaluated.